Unwarranted Trust and Unwarranted Punishment: Scientistic Beliefs Predict Support for Penalizing Science Skeptics - Lukić, Petar; Žeželj, Iris (Primenjena psihologija, 2025)
Contemporary society demands laypeople to articulate their attitudes towards science. Whilst distrust in science undeniably has detrimental outcomes, we argue that its opposite, uncritical trust in science and scientists (i.e. scientism) also leads to potential unwarranted societal polarization. In Study 1 we observed that people who endorsed scientistic beliefs supported discriminatory policies against people who ignore scientific knowledge or promote anti-scientific views, ranging from restrictions on their media appearance to imprisonment and denial of healthcare. Study 2 replicated the effect and tested its potential mechanism: the tendency to moralize rationality mediated the relationship between scientistic beliefs and support for penalizing measures. Our findings demonstrate that unwarranted beliefs, even if positive in their moderate version, are associated with increased support for unwarranted measures against dissenters.